Stress Performance Evaluation of Shield Machine Cutter Head during Cutting Piles under Masonry Structures. (29th April 2022) - Peng, Fei; Ma, Shiju; Li, Mingyu; Fu, Kui
Abstract : In the construction of the metro, the development and operation of large-scale underground space in the city cause the construction of metro tunnels near the original underground structures, and the complex environment for passing structures at close range has increased significantly. Comparing the actual load data of the actual project with the data obtained with the proposed new method, it is proved that the predicted load range corresponds essentially to the measured average curve of the project, which is commonly used with the experimental load formula. Subsequently, the load calculation method is used to guide the construction of the composite base of the protective cutting pile of one of the Zhengzhou metro lines under the existing masonry structure. Based on the existing building damage grade evaluation standards, the professional house inspection agency checked the intersection of the tunnel and the building space and realized that the main structure of the house during the tunnel construction process would be still safe; thereby, Zhenghe Community Building 1# can be used normally after partial repairs.